Controlled Delivery of Illegal Drug Parcels in Scotland: Does Policing Practice Align With a Public Health Approach Focused on Drug-Related Harm? - Morales-Gómez, Ana (Journal of drug issues, 2022)
An increase in the flow of drugs into the UK via international postal systems poses challenges for law enforcement. ‘Controlled delivery’ can be used to disrupt supply networks and secure intelligence for prosecution; however, critics argue that law enforcement should instead focus on reducing drug-related harm. In Scotland, national drugs strategy adopts a public health approach but it is unclear whether this extends to policing practice. Therefore, this paper examines whether controlled delivery of drug parcels aligns with a public health policing approach. We find evidence of alignment in terms of potential harm to individual users, particularly in relation to legal highs, but not in terms of drug-related harms within the communities to which parcels were destined. We argue that further investigation is required in order to assess the extent to which political intent and policing practice in Scotland align around the principles of harm reduction and public health.